2015
DOI: 10.1074/jbc.m115.648642
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ergothioneine Biosynthesis and Its Effect on Mycobacterium tuberculosis Growth and Infectivity

Abstract: Background: Mycobacterium tuberculosis synthesizes ergothioneine, a sulfur-containing molecule with unknown function. Results: egtD encodes for a histidine methyltransferase that is essential for ergothioneine biosynthesis and is negatively regulated through M. tuberculosis serine/threonine protein kinase D. Conclusion: M. tuberculosis modulates intracellular ergothioneine levels in response to starvation. Significance: Mechanisms by which M. tuberculosis senses and adapts to nutrient starvation is essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 59 publications
0
53
0
Order By: Relevance
“…Previously, EgtD has been shown to be required for the biosynthesis of ergothioneine as well as being essential for the growth of Mtb in murine macrophages and animal models. 3739 Analysis of the 446 compounds screened from the NIH clinical collection yielded a hit cutoff of 30.1% activity of EgtD, which produced an initial hit rate of 4.3% (19 compounds, Figure 7A). The hit cutoff was determined by calculating three standard deviations from the average of the entire screening data.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, EgtD has been shown to be required for the biosynthesis of ergothioneine as well as being essential for the growth of Mtb in murine macrophages and animal models. 3739 Analysis of the 446 compounds screened from the NIH clinical collection yielded a hit cutoff of 30.1% activity of EgtD, which produced an initial hit rate of 4.3% (19 compounds, Figure 7A). The hit cutoff was determined by calculating three standard deviations from the average of the entire screening data.…”
Section: Resultsmentioning
confidence: 99%
“…To the extent that ERG is a 'secondary' metabolite, defined (88) as a molecule whose synthesis has a relatively restricted distribution in different organisms, the biosynthetic pathways diverge from primary metabolism via the amino acids histidine, cysteine and methionine (89)(90)(91)(92)(93)(94) . Thus (Fig.…”
Section: Biosynthesis and Phylogenetic Distributionmentioning
confidence: 99%
“…However, despite considerable effort, roles for EGT in Mtb and its potential involvement in redox homeostasis and pathogenesis remain unknown. Recently we have shown that EGT levels in Mtb are modulated by protein phosphorylation during transition into late states of growth (Richard-Greenblatt et al, 2015), yet it is still unclear why mycobacteria produce both EGT and MSH to maintain redox homeostasis.…”
Section: Introductionmentioning
confidence: 99%